1980
DOI: 10.1126/science.210.4476.1347
|View full text |Cite
|
Sign up to set email alerts
|

"Atmospheric" Epoxidation of Benzo[ a ]pyrene by Ozone: Formation of the Metabolite Benzo[ a ]pyrene-4,5-Oxide

Abstract: Benzo[a]pyrene deposited on a glass fiber filter reacts rapidly in the dark or light with ambient levels of ozone to yield a mixture of products that display strong direct mutagenicity in the Ames assay. The major stable contributor to this activity has been identified as benzo[a]pyrene-4,5-oxide, a DNA-binding metabolite in biological systems, known to be a strong direct mutagen with Salmonella typhimurium strain TA98.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0
3

Year Published

1981
1981
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(84 citation statements)
references
References 23 publications
3
78
0
3
Order By: Relevance
“…Five and more rings PAHs tend to be mainly associated with particles having size <1 mm (Kahan et al, 2006;Gross and Bertram, 2008;Pitts et al, 1980;Vione et al, 2004). These pollutants have received considerable research attention since they have mutagenic and carcinogenic effects on humans (Pitts et al, 1980;Kou et al, 2008). The oxidized PAH derivatives are more toxic than their parent compounds because hydrophilic molecules are more easily reabsorbed in the alveolus (Barring et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five and more rings PAHs tend to be mainly associated with particles having size <1 mm (Kahan et al, 2006;Gross and Bertram, 2008;Pitts et al, 1980;Vione et al, 2004). These pollutants have received considerable research attention since they have mutagenic and carcinogenic effects on humans (Pitts et al, 1980;Kou et al, 2008). The oxidized PAH derivatives are more toxic than their parent compounds because hydrophilic molecules are more easily reabsorbed in the alveolus (Barring et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Three-to four-ring PAHs are semi-volatile and these compounds partition between the gas and solid phases in the atmosphere (Sitaras et al, 2004). Five and more rings PAHs tend to be mainly associated with particles having size <1 mm (Kahan et al, 2006;Gross and Bertram, 2008;Pitts et al, 1980;Vione et al, 2004). These pollutants have received considerable research attention since they have mutagenic and carcinogenic effects on humans (Pitts et al, 1980;Kou et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic compounds (PAHs) are ubiquitous in the environment and known as having mutagenic and carcinogenic effects on human body (Pitts et al, 1980). They are emitted into the atmosphere mainly through incomplete combustion of fossil fuels and biomass burning.…”
Section: Introductionmentioning
confidence: 99%
“…In the atmosphere, the PAHs with less than 3 rings are partitioned between the gas and solid phases due to their relatively higher vapor pressure (Calvert et al, 2002), while the PAHs with more than 3 rings are mainly found in the particulate phase, primarily associating with particles having size < 1 mm (Pitts et al, 1980). The ozonation of PAHs has long been attracting much attention due to the resulted alteration to the chemical and toxic properties of PAHs (Pitts et al, 1978(Pitts et al, , 1980. Up to now, numerous studies on reactions of PAHs with ozone, which can be roughly separated into two fields, have been carried out, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This difficulty in measuring palmitoleic acid in the atmosphere could be due to its low emission rate compared to oleic acid, to its higher volatility and possible degradation in the gas phase, or to heterogeneous attack on the double bond by ozone or other radicals yielding, in part, aliphatic dicarboxylic acids, as suggested by several researchers [e.g., Kawamura .g., fluoranthene, pyrene, and others) show concentrations significantly lower than emission data would suggest. This suggests that such low molecular weight PAH may preferably degrade in the gas phase by photochemical processes and radical attack [Kamens et al, 1990;Pitts et al, 1969Pitts et al, , 1978Pitts et al, , 1980Pitts et al, , 1985Lane and Katz, 1977;Pan Cauwenberghe, 1983], which leads in turn to further volatilization of such particle phase associated PAH in an attempt to restore the gas-particle phase equilibrium. Alternatively, the low molecular weight PAH may be degraded by heterogeneous chemical reactions between gas phase oxidants and particle phase PAH.…”
Section: Organic Compound Aerosol Source Profilesmentioning
confidence: 99%